Sistem Informasi Penunjang Proses Pemesanan dan Desain Kue Pada Toko Kue Artisan Online Berbasis Web - Tania Jovita Wibowo; Suryasari Suryasari; Arnold Aribowo; Andree E. Widjaja (ULTIMA InfoSys, 2019)
Along with the development of times, artisan cakes are increasingly in demand by the public to celebrate special days or as a gift. Online artisan cake is a cake shop that uses social media like Instagram and Facebook to sell their cakes. The current cake ordering process is still done manually which is done through two stages. First, customer sees and chooses the type and design of cakes through Instagram or Facebook. Second, he or she places an order on the cake selected before via Line or WhatsApp. The need of two different media makes the ordering system less efficient. Apart from that, customer who want to make special or custom requests can only deliver their request through messages via Line or WhatsApp, so there are often misunderstanding and inaccuracies caused by either customer or cake maker different picture of request. Therefore, an information system is needed to support the order process and cake design at online artisan cake shops using Rapid Application Development (RAD) system development using prototyping. System modeling is developed by using UML 2.5, namely use case diagrams, activity diagrams, class diagrams and entity relationship diagrams. The final result of this final project is a website that supports ordering process and cake design at online artisan cake shops that can simplify the ordering process and order customization on the design of the ordered cakes. The website created has gone through the test phase and is ready to use.